PONDOK PESANTREN DAN MENGEMBANGKAN KUALITAS SUMBER DAYA MANUSIA - Indana Zuhrotul Maulidah (Universitas Islam Malang, 2021)
Human Resources (HR) has a very important position in realizing development capacity, which places humans in their function, namely as a development resource. The purpose of this study was to determine the efforts made by the Pondok Pesantren Darussalam Banyuwangi in developing the quality of human resources, to determine the supporting and inhibiting factors faced by the Darussalam Islamic Boarding School in developing the quality of human resources. To achieve these objectives, researchers used a qualitative research type with descriptive methods. The results showed that; (1) The existing education and teaching system in the Darussalam Islamic Boarding School, namely using the formal education system, non-formal education, and extracurricular education, (2) The efforts of the Darussalam Islamic Boarding School in developing quality human resources, which can be proven by the existence of various activities. and the educational activities in it, of which all these educational programs and activities are in order to develop the quality of faith, science and other skills of the students or students, from which all these resources can be created. quality human resources, (3) Supporting and Inhibiting Factors of Darussalam Islamic Boarding School in developing the quality of human resources, divided into internal factors and external factors.